Analisis Kemampuan Literasi Matematika Mahasiswa Tadris Matematika UIN Sulthan Thaha Saifuddin Jambi dalam Menyelesaikan Soal Aljabar Linear Elementer Materi Matriks - Asiani, Rosi Widia (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
ABSTRACT Literacy is one of the most important skills in learning mathematics in this century. Students who have good literacy skills will be able to formulate and solve problems that exist in everyday life, perform mathematical manipulations and then provide interpretations as answers to these problems. This study aims to see the mathematical literacy ability of students in solving elementary linear algebra problems, especially on matrix material. The research method used is descriptive method with a qualitative approach. The data analysis technique uses Spradley theory, namely domain analysis with test results, taxonomic analysis through interviews and componential analysis, namely comparing the results obtained with previous research. The results of the study, it was found that students with high-level mathematical abilities had met the three indicators of mathematical literacy ability. Students with moderate ability levels fulfill the first indicator, but the second and third indicators are only partially fulfilled. Meanwhile, students with low levels of ability have not met the three indicators. This research is expected to provide an overview of students' mathematical literacy skills and as a consideration for choosing the right learning strategies so that students' literacy skills can increase.